2021
DOI: 10.3389/fmars.2021.690764
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Suspended Particulate Matter, Nutrient, and Salinity on the Growth of Amphidinium carterae Under Estuary Environmental Conditions

Abstract: The environmental conditions in estuaries display distinct variability along the river-ocean mixing continuum from turbid, eutrophic freshwater to clear, oligotrophic offshore oceanic water. In order to understand the effects of suspended particulate matter (SPM), nutrient, and salinity on phytoplankton growth, this study investigated the response of a harmful dinoflagellate (Amphidinium carterae Hulburt) to the ecological gradients in estuary environments. Rapid nutrient uptake and growth of A. carterae were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…For conservative nutrients, salinity can be used as a proxy to indicate the mixing processes affecting nutrient distribution (Liss, 1976). In dynamic environments, such as the ocean, many physical and biogeochemical processes including coastal upwelling, biological processes (e.g., nutrient uptake), remineralization, desorption, and adsorption of nutrients on settling particles (e.g., Carstensen et al, 2020;Jiang et al, 2021) cause relationships between salinity and nutrient concentrations to deviate from conservative behavior. Therefore, the use of salinity as a proxy for land-based nutrient inputs may not fully reflect nutrient distributions.…”
Section: February 20th 2010-southwesterly Windsmentioning
confidence: 99%
“…For conservative nutrients, salinity can be used as a proxy to indicate the mixing processes affecting nutrient distribution (Liss, 1976). In dynamic environments, such as the ocean, many physical and biogeochemical processes including coastal upwelling, biological processes (e.g., nutrient uptake), remineralization, desorption, and adsorption of nutrients on settling particles (e.g., Carstensen et al, 2020;Jiang et al, 2021) cause relationships between salinity and nutrient concentrations to deviate from conservative behavior. Therefore, the use of salinity as a proxy for land-based nutrient inputs may not fully reflect nutrient distributions.…”
Section: February 20th 2010-southwesterly Windsmentioning
confidence: 99%
“…Suspended solids have also been blamed for damaging the fish gills and their visibility underwater [11]. High suspended particle also causes the marine and freshwater plant to get insufficient sunlight [12]. Due to this concern, an approach using spatial interpolation techniques can be used to monitor TSS in the aquatic ecosystem.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In particular, low salinities cause the increase of mortality of plankton species, depending on their salinity resistance [55]. Silicates (Si-SIO4) are major nutrients for siliceous primary producers (diatoms), which can become limiting factors in oligotrophic areas such as the Greek seas (similar to the rest of the Mediterranean Sea, with values starting from 1-3 μM in the west and reaching 0.003 μM in the Levantine basin) [56]. Most of the silicon inputs (up to 80% on a global scale) in the marine environment come from continental discharges, from both surface water (rivers mostly) and groundwater [56], though recently, it has been shown that beach weathering contributes to Si [57].…”
Section: Importance Of Parametersmentioning
confidence: 99%
“…Demand for Si by primary producers is limited only to diatoms that require Si as much as N and P. A study in a Mediterranean coastal ecosystem showed that salinity affects the concentration of silicates, and in particular, high salinities correspond to low silicate concentrations [56]. This, combined with the high filtration of silicates along the sediments surrounding the underground discharges, results in a concentration of Si in the coastal waters which is less than 3.5% of the initial concentration in the groundwater (freshwater), and following a cycle of subterranean mixing, it can reach the inner shelf at even lower concentrations of 2.2% [56,60]. The Bayesian-CHAID model resulted in the inclusion of silicates in the group of important parameters, obviously due to its relation to salinity and its classification as a limiting factor, as well as since together with N and P, in the various forms that Salinity, together with temperature, has been reported that governs phytoplankton communities (hence chl-a and eutrophication), especially in diatom and cyanophytedominated communities [52].…”
Section: Importance Of Parametersmentioning
confidence: 99%
See 1 more Smart Citation